Ethanol Postpolymerization Treatment for Improving the Biocompatibility of Acrylic Reline Resins. (18th July 2013) - Neves, Cristina B.; Lopes, Luís P.; Ferrão, Helena F.; Miranda, Joana P.; Castro, Matilde F.; Bettencourt, Ana F.
Abstract : Objective . To evaluate the effect of postpolymerization treatment based on ethanol-aqueous solutions on the residual monomer (RM) content, flexural strength, microhardness, and cytotoxicity of hard chairside reline resins (Kooliner, Ufi Gel Hard). Methods . After polymerization, specimens were immersed in water, 20%, 50%, or 70% ethanol solutions at 23°C or 55°C for 10 minutes. Controls were left untreated. HPLC was used for the determination of RM content. Specimens were submitted to Vickers microhardness and 3-point loading flexural strength tests. Cytotoxicity of resin eluates was determined on human fibroblasts by assessing cellular mitochondrial function and lactate dehydrogenase release. Results . Higher concentrations of ethanol promoted lower RM content at 55°C in both materials. The mechanical properties were maintained after 50% and 20% ethanol treatments in Kooliner and Ufi Gel Hard, respectively. Specimens submitted to those treatments showed significant reduction on cytotoxicity compared to immersion in hot water, the treatment of choice in the recent literature. Significance . Immersion of relined dentures in specific ethanol solutions at 55°C for 10 minutes can be considered an effective postpolymerization treatment contributing to increase materials biocompatibility. The proposed protocol is expeditious and easy to achieve with simple equipment in a dental office.